A critical evaluation of current protocols for the follow-up of women treated for gynecological malignancies: A pilot study. Issue 5 (1st September 2001) - Olaitan, A.; Murdoch, J.; Anderson, R.; James, J.; Graham, J.; Barley, V.
Abstract : This retrospective review was undertaken to determine the efficacy of routine follow-up in the detection and management of recurrent cancer. The case notes of all women attending a regional cancer center who were diagnosed with cancer in 1997 were reviewed. Of 81 new cancers followed up for a median of 42 months (range 36–48), 14 have recurred after curative treatment and there were six cases of persistent disease. The median number of clinic visits per patient was 3.5 (range 1–16). Eight recurrences (57.1%) were diagnosed at scheduled outpatient appointments, three (2 l.4%) presented to the general practitioner (GP), and three were seen as emergencies in hospital. Seventeen patients with persistent/recurrent disease have died and three are alive with disease. The median time from initial presentation to disease recurrence was 12 months (range 5–25) and the median time from recurrence to death was 5 months (range 1–20). The longest interval between onset of symptoms and diagnosis of recurrence (4 months) occurred in those presenting at scheduled outpatient clinics. This study demonstrates that the current follow-up protocol is associated with delays in diagnosing recurrence, because symptomatic patients postpone seeking help until their scheduled visit. We have therefore commenced a prospective study evaluating other models of follow-up.